IMPLEMENTASI SAND FILTER DAN CARBON FILTER DALAM MENGOPTIMALKAN KUALITAS AIR BERSIH DI ASRAMA TOWER - Ibnu Miftakhul Azis; Yenni Arnas; Inof Seno Acton (Politeknik Penerbangan Indonesia Curug, 2018)
At this time in the STPI Curug Tower Dormitory has one source of clean water that comes from well water / land and is used to meet the needs of clean water in the Tower Dormitory. Currently for the clean water quality in the Tower Dormitory itself is not so maximal, there are several parameters that almost exceed the maximum standard of clean water that is allowed. Clean water filtration design using sand filter and carbon filter method in STPI Curug Tower Dormitory. The design created has been successfully carried out and in accordance with the desired. This design was made to maximize the quality of clean water in the Tower Dormitory